Instructional strategies in bedside teaching sessions in public sector hospitals in Iraq - Salih Mohammad, Suzan; Paramasivam, Shamala; Darmi, Ramiza; Ibrahim, Normala (Secholian Publication, 2022)
Bedside teaching is an effective and commonly used teaching method in medical education. However, few studies have analyzed the language and instructional strategies used during real-life interactions in bedside teaching sessions. Past research investigated the effectiveness of bedside teaching methods from medical instructors’ and students’ perspectives and the influences of the relationships between instructors and students on the success of this teaching method. This study sheds light on the discourse of bedside teaching in Iraqi hospitals from a linguistic perspective. The data were collected qualitatively in the form of 26 video recordings of medical instructors and medical students in interactions in two public hospitals in the Kurdistan region of Iraq during bedside teaching sessions and were analyzed in a mixed method technique. Discourse analysis was the research design and Nilsson et al. (2010) classification for instructional strategies was used as the analytical framework of the study. The findings revealed that seven instructional strategies associated with various pragmatic functions were employed by the instructors. The findings imply that the use of proper and effective instructional strategies that suit communicative medical events would have an impact on the understanding, expectations, and situational needs of medical students. The findings have pedagogical implications relevant to the fields of medical education and applied linguistics. This study represents a pioneering attempt to analyze bedside teaching sessions in an Iraqi context. It could therefore form a basis and starting point for future research in the fields of medical education and applied linguistics.